Do Institutions Receive Favorable Allocations in IPOs with Better Long-Run Returns? - Boehmer, Beatrice; Boehmer, Ekkehart; Fishe, Raymond P. H. (Journal of Financial and Quantitative Analysis, 2006)
Abstract We analyze allocations to institutional and retail investors in 441 initial public offerings (IPOs). In addition to the well-known favorable first-day returns, we show that institutions also obtain more allocations in IPOs with better long-term performance. We find that initial institutional flips help predict future returns, suggesting that at least some institutions retain valuable private information about IPO firms. Collectively, these findings illustrate the importance of aftermarket relations between underwriters and investors and that underwriters have discretionary means to compensate IPO investors beyond first-day returns and price stabilization.